Shell and tube heat exchanger flexible design strategy for process operability - Liang-Yu Chen; Vincentius Surya Kurnia Adi; Rosalia Laxmidewi (Case Studies in Thermal Engineering, 2022)
Traditionally, the shell and tube heat exchanger (STHE) design minimizes the total annual cost subject to allowable pressure drop. However, it is often insufficient when considering equipment limitations and uncertain disturbance factors. Design inefficiency or improper operation of overall process systems could potentially occur. A rigorous design strategy of STHE based on the flexibility index analysis method is proposed to address the above issues. The genetic algorithm with rigorous constraints is considered for the STHE design optimization. Simultaneously, the flexibility index (FI) is incorporated to quantify the uncertain factors of the STHE operation. The STHE load capacity and the corresponding uncertain disturbance factors affecting the STHE operability are evaluated. In addition, design workflows incorporating flexibility index are also discussed. Simultaneous consideration of the flexibility index in the optimization procedure can improve the STHE design operability under the expected range of disturbance factors and lower the total cost.